The Harriet Lane handbook : The Johns Hopkins hospital - Kleinman, Keith (Elsevier, 2021)
The 22nd Edition of this portable reference continues to be the #1 source of pediatric point-of-care clinical information. Updated and expanded content includes an all-new chapter on Psychiatry, plus reorganized information on Emergency and Critical Care Management, as well as Traumatic Injuries. The popular Pediatric Drug Formulary, updated by Carlton K. K. Lee, PharmD, MPH, provides the latest in pharmacologic treatment of pediatric patients.